A minichromosome of LGVI from crossing two quasi-terminal reciprocal translocations - Robert L Metzenberg; M J Orbach (Fungal Genetics Reports, 2000)
Non-reciprocal translocations, in which one chromosome is a pure donor and another is a pure recipient, have found abundant uses in genetics, molecular biology, and cytology (Perkins 1997Advances in Genetics 36:239-398). Our original aim was to prepare a strain carrying a chromosome truncated in both arms, with the idea that such a small chromosome would be easily purified by pulsed field electrophoresis and would be a good preliminary substrate for genomic sequencing.